SILICA TRANSPORT AND GROWTH OF HIGH-TEMPERATURE CRYSTALLINE QUARTZ IN SUPERCRITICAL AQUEOUS FLUIDS - Balitsky V.S.; Balitskaya L.V.; Ivasaki H.; Ivasaki F. (My University, 1999)
Silica transport and seed growth of high-temperature quartz in pure water and various aqueous fluids (pH from 1 to 12) were experimentally studied at temperatures from 580 to 1100°C and pressures from 0.2 to 5 kbar under positive temperature gradient (ΔT) conditions. It was shown that throughout the whole aforesaid range of P and T values the direction of silica transport in pure water, neutral and alkaline fluids is identical to that of the positive temperature gradient (ΔT). However, in the acid fluoride fluids the direction of the silica transport changes to the opposite at P less than 0.8-1 kbar. This is related to the ambiguous and varied influence of the fluid temperature and density on the acidity constant of hydrofluoric acid, which controls quartz solubility. Synthesized crystals have stable hexagonal bipyramidal {101 1} and prismatic {101 0} faces, which are characterized by approximately similar growth rates and define short-prismatic and bipyramidal crystal habit, as well as bipyramidal faces with higher indices {h0h̄ 1}. Development of the latter results in elongated bipyramidal habit. Introduction of trace components to high-temperature quartz first allowed us to synthesize its violet-pink variety.